2005
DOI: 10.1149/1.1921133
|View full text |Cite
|
Sign up to set email alerts
|

High Specific-Energy Lead-Acid Batteries Through Organic Metals

Abstract: A novel room-temperature route to corrosion protect lead-coated plastic grids with an organic metal, namely, polyaniline, for producing commercial-grade high specific-energy 12 V/45 Ah lead-acid batteries is reported. The specific energy of these leadacid batteries is found to be ca. 45 Wh/kg as against about 30 Wh/kg for conventional lead-acid batteries. It is believed that the study reported here will open up a new realm of possibilities for lead-acid battery development, and will contribute directly towards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…z A maximum specific energy of 49 Wh kg -1 is in excellent agreement to the data reported by HARIPRAKASH et al and MARTHA et al, 6,7 which are by best of knowledge the highest figures reported for the specific energy of lead acid batteries so far.…”
Section: She --------------------------------------------------------supporting
confidence: 89%
“…z A maximum specific energy of 49 Wh kg -1 is in excellent agreement to the data reported by HARIPRAKASH et al and MARTHA et al, 6,7 which are by best of knowledge the highest figures reported for the specific energy of lead acid batteries so far.…”
Section: She --------------------------------------------------------supporting
confidence: 89%
“…Polyanilines have been studied extensively due to the fundamental interest in reaction mechanisms and for their applications to practical devices for energy storage, electrochemical sensors, electrochromic devices, EMI shielding, corrosion protection and others (Kobayashi et al 1984;DeBerry 1985;Kitani et al 1986;Genies et al 1988;Zhou et al 1990;Baxskai et al 1993;Chen et al 1996;Hugot-Le-Goff 1997;MacDiarmid 1997;Park 1997;Trivedi 1997;Malinauskas 1999;Wang and Jing 2005). Application of CPs in energy storage devices is well known (Conway 1999) and recent studies (Hughes et al 2002;Gupta and Miura 2005;Martha et al 2005;Peng et al 2006) in this area gave impetus to fundamental and applied research on CP-based new materials.…”
Section: Introductionmentioning
confidence: 99%
“…Electropolymerized polyaniline films have been used to improve the corrosion resistance of the lead acid battery current collector [1]. However, very little information was provided in this earlier study on the nature of the resulting film present at the lead electrode surface.…”
mentioning
confidence: 99%
“…In this work, polyaniline deposits were formed by different methods in an aqueous 1.5 M H 2 SO 4 solution containing the aniline monomer [1,2]. The morphology of coatings and their chemical composition were characterized by scanning electron microscopy and X ray photoelectron spectroscopy, respectively.…”
mentioning
confidence: 99%